2023
DOI: 10.1001/jamainternmed.2023.0780
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Herbal-Based Injection on 28-Day Mortality in Patients With Sepsis

Abstract: ImportancePrevious research has suggested that Xuebijing injection (XBJ), an herbal-based intravenous preparation, may reduce mortality among patients with sepsis.ObjectiveTo determine the effect of XBJ vs placebo on 28-day mortality among patients with sepsis.Design, Setting, and ParticipantsThe Efficacy of Xuebijing Injection in Patients With Sepsis (EXIT-SEP) trial was a multicenter, randomized double-blind, placebo-controlled trial conducted in intensive care units at 45 sites and included 1817 randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…We do not think that drug equivalence or noninferiority trials are the next step because our study allowed for antibiotics and optimal sepsis management (eg, fluid resuscitation), and there is no well-accepted adjuvant treatment for sepsis. However, we do agree with Dr Hu that a large randomized clinical trial outside of China would be the best pathway to demonstrate the value of Xuebijing injection use in the rest of the world.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…We do not think that drug equivalence or noninferiority trials are the next step because our study allowed for antibiotics and optimal sepsis management (eg, fluid resuscitation), and there is no well-accepted adjuvant treatment for sepsis. However, we do agree with Dr Hu that a large randomized clinical trial outside of China would be the best pathway to demonstrate the value of Xuebijing injection use in the rest of the world.…”
mentioning
confidence: 99%
“…In Reply We appreciate Dr Hu’s interest in and thoughtful criticism of our clinical trial . We agree that it will be challenging to get Xuebijing approved outside of China, but that the obstacles are surmountable…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To the Editor A recent study by Liu and colleagues reported a reduction in 28-day mortality in patients with sepsis treated with Xuebijing (XBJ), a Chinese medicine compounded injection, compared with placebo. In fact, XBJ has been used in the Chinese market for almost 20 years since its approval in 2004, and it was approved by the National Medical Products Administration of China for the treatment of severe COVID-19 in 2020.…”
mentioning
confidence: 99%
“…Lastly, in the study by Dr Liu and colleagues, XBJ was compared with placebo and seemed to be associated with reduced mortality. However, there is still a lack of high-quality drug equivalence and noninferiority trials of XBJ.…”
mentioning
confidence: 99%